The effect of peer victimization on adolescents’ revenge: the roles of hostility attribution bias and rumination tendency - Zhao, Xu-Yan; Zheng, Shu-Jie (Frontiers in Psychology, 2024)
Although previous studies revealed that peer victimization was closely related to revenge, mechanisms underlying this association have been unclear. The purpose of this study is to examine the mediating role of hostility attribution bias (HAB) and the moderating role of rumination tendency in the relationship between peer victimization and revenge. The data were collected from 6622 adolescents. The PROCESS macro of SPSS 26.0 was used to examine the hypotheses. The results show that peer victimization positively associates with revenge. Hostile attribution bias play a partial mediating role between peer victimization and revenge. Both the direct effect of peer victimization on revenge and the first half of the mediating effect of HAB are moderated by rumination tendencies. Specifically, both direct and indirect effects of peer victimization on revenge are stronger in individuals with concrete experiential rumination (CER) tendency than in those with abstract analytic rumination (AAR) tendency .